1960
DOI: 10.1104/pp.35.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Lateral Movement of Phosphorus 32 in Peppermint

Abstract: Auchter (1) that occurs when a peppermint plant is fedl through a specific portion of its root system. MATERIALS AND AIETHODSThe square stem of peppermiiint, when allowed to root, characteristically (levelops roots at each of the four corners of the stemii allowing a rather ideal separation of the four miiain vascular bundlles.Peppermint stock plants were grown in the greenhouse under a short (lay photoperiod to maintain the plants in a vegetative con(lition. Cuttings were ma(le from the stock plants at vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1961
1961
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…This is further demonstrated by the greatest concentration of these elements being centred in the actively growing regions of the plant, e.g., foliage and roots compared to stem tissue components. In contrast, calcium which is largely nonmetabolically absorbed and accumulated in the plant, was most greatly concentrated in the stem tissue, and increases in the phosphorus supply did not result in a corresponding increase in calcium concentration (see also Biddulph et al 1958, Rinne and Langston 1960, Moore et a! 1961.…”
Section: Chemical Compositionmentioning
confidence: 92%
“…This is further demonstrated by the greatest concentration of these elements being centred in the actively growing regions of the plant, e.g., foliage and roots compared to stem tissue components. In contrast, calcium which is largely nonmetabolically absorbed and accumulated in the plant, was most greatly concentrated in the stem tissue, and increases in the phosphorus supply did not result in a corresponding increase in calcium concentration (see also Biddulph et al 1958, Rinne and Langston 1960, Moore et a! 1961.…”
Section: Chemical Compositionmentioning
confidence: 92%
“…The net effect is greater nutrient uptake by those roots. Although it is commonly assumed that nutrients taken up by individual roots will be transported throughout the plant, there is evidence that the transport of nutrients within a plant can be sectorialpreferentially transported from roots or leaves to specific tissues with the most direct vascular connections (Rinne and Langston 1960;Hay and Sackville Hamilton 1996;Orians et al 2002;and reviewed by Murray et al 1982;Watson and Casper 1984;Orians and Jones 2001;Orians et al 2002). Orians et al (2002) manipulated nutrient levels to two different root zones of split-root tomatoes, and found that leaves vertically aligned above the fertilized lateral roots had direct vascular connections to those roots, were larger, and had lower concentrations of phenolics than did leaves without direct vascular connections.…”
Section: Introductionmentioning
confidence: 99%
“…port of resources from shoots to roots (Cook and Stoddard, 1960;Steiber and Beringer, 1984;Singleton and van Kessel, 1987;Murphy and Watson, 1996) and from roots to shoots (Rinne and Langston, 1960;Hay and Sackville Hamilton, 1996) is also prevalent. For example, Rinne and Langston (1960) performed split-root studies and showed that the movement of phosphorous isotope (P 32 ) was confined to leaves and sides of leaves orthostichous to the labeled roots.…”
mentioning
confidence: 97%
“…For example, Rinne and Langston (1960) performed split-root studies and showed that the movement of phosphorous isotope (P 32 ) was confined to leaves and sides of leaves orthostichous to the labeled roots. These shortterm isotope experiments suggest that spatial variation in the availability of soil nutrients might result in heterogeneity in plant growth and traits important to herbivores.…”
mentioning
confidence: 99%